DOKTRIN PENCIPTAAN DAN TANGGUNG JAWAB EKOLOGIS GEREJA DI ABAD KE-21 - Juliana Cancer Denasita; Tesalonika, Marni Liku Dengen, Merlin, Dwy Giovani Tonapa (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article examines the doctrine of creation as the foundation of ecological theology and its implications for the church's responsibility in addressing the ecological crisis in the 21st century. The doctrine of creation affirms that all creation is God's good work, thus humans are called to cultivate and care for the earth, not exploit it. From this perspective, the church has a strategic role in integrating ecological spirituality into its teaching, liturgy, and social practice. Ecological education, or eco-literacy, is a crucial instrument in shaping the congregation's ecological awareness, enabling Christian faith to be realized through concrete actions in preserving the integrity of creation. However, the implementation of the church's ecological responsibility still faces challenges, such as limited theological understanding, resistance to lifestyle changes, and minimal policy support. Therefore, the church is required to present a contextual, creative, and collaborative approach in responding to ecological issues. This article also emphasizes the global relevance and local contextualization of ecological theology, which positions the church as part of a universal movement to care for the earth and as an agent of transformation in addressing environmental challenges unique to Indonesia. Thus, the doctrine of creation has not only dogmatic value but also practical significance in building ecological awareness rooted in Christian faith